EVALUASI KEBIJAKAN SISTEM PEMERINTAHAN BERBASIS ELEKTRONIK DALAM PELAYANAN ADMINISTRASI (SIOLA) DI KEMENTERIAN DALAM NEGERI REPUBLIK INDONESIA - Agus Widiyarta; Hilmi Izaz Robbani; Choiriyah Eka Windiastuti (Jurnal Penelitian Administrasi Publik, 2020)
Through a policy issued by the Ministry of Administrative Reform and Bureaucratic Reform (Permenpan No.5 Year 2018) concerning Guidelines for Evaluation of Electronic-Based Government Systems (SPBE). This study uses the Dunn evaluation with the aim of describing the SPBE policy evaluation in the Ministry of Home Affairs with the SIOLA application. Descriptive qualitative research methods. interview data collection, observation, and literature review. The results showed that the Electronic-Based Government System (SBPE) through the application of SIOLA was not optimal because there was still a digital divide that caused a lack of cohesiveness between the local government and the Ministry of Home Affairs. To support the improvement of the SPBE Policy, employees are evenly given training in the use of technology related to public services, developing the Ministry of Home Affairs SIOLA application in accordance with the provisions and various services listed in Permenpan No. 5 of 2018. As well as the socialization of the SIOLA application SPBE policy to all Indonesian regional governments that support the improvement of the quality of public services.